Dostrzegać niestworzoną miłość poprzez Prawdę, Dobro i Piękno w rozproszonym świecie, według Pawła Fłorenskiego - Kotkowska, Elżbieta (Poznańskie Studia Teologiczne, 2009)
Physical research shows us that our world is more and more scattered. This experience of the physical dispersion or the disappearance of what seemed to be permanent is also transferred into the world of values. The hierarchy of values generally accepted in the past yields to dispersion. Sensible references to the act of creation as God’s work also disappear. Emphasis is placed on the temporal beginning of our Universe (Big Bang) and people do not think of the ontological (en arche) or theological primeval beginning. How should we to rebuild a uniting vision of the world? It seems useful to appeal to father Pavel Alexandrovich Florensky, a representative of Orthodox theology. He thought over and worked on the definition of God's Love all his life, because it is love and acceptance that people really need in a scattering world, especially the Love, which we experience in the act of creation. What was characteristic of father Pavel was his meditative view on the overall unity of what is and is cognizable in the scientific, aesthetic or moral mode. It is only in those three ways taken together that we can recognize God’s creation and His Love. He is very similar in his approach and conclusions to another theologian Hans Urs von Balthasar. They both say together that first principle in the act of creation is love and we can recognize it through the Beauty, Truth and Good in the World and people’s relations.